(untitled) - Hislop, Helen J. (Philadelphia, 2002)
Daniels and Worthingham's Muscle Testing is the original handbook of manual evaluation of muscular strength. In addition to offering tried and true methods for assessing and grading skeletal muscle function, this up-to-date classic provides a comprehensive section on muscle anatomy and innervation that rounds out the testing chapters by linking muscle topography and function. Beautifully illustrated with more than 575 high-quality drawings, the 7th edition includes over 100 new drawings created specifically for this edition
Keywords: Muscle strength,Sức mạnh cơ bắp,Cơ bắp,Muscles; Testing,Thử nghiệm,Kiểm tra,Examination